For x R−{0, 1}, let f1(x)= , f2(x)=1−x and f3(x) be there given functions. If a function, J(x) satisfies (f2 J f1)(x)=f3(x) then J(x) is equal to
a. |
f3(x) |
b. |
f1(x) |
c. |
f2(x) |
d. |
f3(x) |
For x R−{0, 1}, let f1(x)= , f2(x)=1−x and f3(x) be there given functions. If a function, J(x) satisfies (f2 J f1)(x)=f3(x) then J(x) is equal to
a. |
f3(x) |
b. |
f1(x) |
c. |
f2(x) |
d. |
f3(x) |
Given f1(x)= ,f2(x)=1−x and f3(x)=
(f2 J f1)(x)=f3(x)
(f2 (J(f1(x)))=f3(x)
f2 =
I−J =
J =1− = =
Now x
J(x)= f3(x)